Literasi Teknologi Pemasaran Digital Petani Kopi Dalam Peningkatan Penjualan Di Desa Kacaribu Kab. Karo, Sumatera Utara - Hasibuan, Annalisa Sonaria; Destiadi, Rezha; Chan, Andi Supriadi; Surbakti, Enda Yunita (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2025)
Coffee is one of the most profitable communities in Indonesia. In addition to being a foreign exchange earner, coffee farming also absorbs a lot of labor and is the main source of income for farmers, especially in coffee centers. North Sumatra Province is one of the centers of Arabica coffee with an area of ​​79,388.64 hectares and a total production of 71,588 tons, and Robusta coffee with an area of ​​17,778 hectares and a production of 9,283 tons. Karo Regency, with an area of ​​9,210 hectares and a coffee production of 7,411 tons, has great potential in coffee production, especially Karo coffee which is in demand in the international market. However, farmers in Kacaribu Village face obstacles in low digital literacy which hinders global marketing. Lack of knowledge about brand identity and digitalization of promotions makes coffee sales less competitive. Digitalization of marketing through digital technology can increase efficiency and market access. This Community Service (PKM) can increase the digital literacy of coffee farmers through training and mentoring, so that it is expected to have a positive impact on coffee farmers in Kacaribu Village, increase income and expand the reach of the Karo coffee market.